Application of Modern Technology: Perspective of Country Tourism Office (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
Social media are considered as one of the most significant data source of modern times. Among numerous industries affected by social media impact, tourism emerges as one of the key sectors where social media are progressively relevant. It has the impact on both destinations and enterprises. Data analytic systems help us to make smarter, data-driven decisions. Now that smartphones are broadly used, analytics systems are developed as mobile applications. The main objective of this paper is to examine the increasing role of the social media data analytics in tourism by presenting the case study on country tourism offices of Slovenia and Croatia. Both descriptive statistics and content analysis were used in order to explore, interpret and compare insights from social media provided by data analytics mobile application. Assorted practical implications have revealed from the study report, such as suggestions for content and the time and day of publishing in order to get higher engagement. Furthermore, no one, to the best of our knowledge, conducted similar research, so the paper contributes to the theoretical development of the field as well.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.